2016
DOI: 10.1063/1.4940588
|View full text |Cite
|
Sign up to set email alerts
|

Coda wave interferometry for the measurement of thermally induced ultrasonic velocity variations in CFRP laminates

Abstract: Ultrasonic velocity measurement is a well-established method to measure properties and estimate strength as well as detect and locate damage. Determination of accurate and repeatable ultrasonic wave velocities can be difficult due to the influence of environmental and experimental factors. Diffuse fields created by a multiple scattering environment have been shown to be sensitive to homogeneous strain fields such as those caused by temperature variations, and Coda Wave Interferometry has been used to measure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…When the effective velocity change is local, or at least not distributed over the area where the CWI method is sensitive, the time lag could deviate from a linear evolution. This relation is experimentally verified in several works when considering a pure dilatation of the materials under thermal effects [19,24] or studying weak stress effect in heterogeneous samples such as concrete [25].…”
Section: Coda Wave Interferometry Theorysupporting
confidence: 52%
See 2 more Smart Citations
“…When the effective velocity change is local, or at least not distributed over the area where the CWI method is sensitive, the time lag could deviate from a linear evolution. This relation is experimentally verified in several works when considering a pure dilatation of the materials under thermal effects [19,24] or studying weak stress effect in heterogeneous samples such as concrete [25].…”
Section: Coda Wave Interferometry Theorysupporting
confidence: 52%
“…Here, all the raw signals (coda part) have the same total length T t = 400µs and sampling time Δt = 0.002 µs. As mentioned in [16,19] when the perturbation in the sample is small, the relative velocity change of the coda part in the signal can be considered as constant. In this configuration the time lag increases linearly with the arrival time.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The high sensitivity of the CWI method has been validated in detecting stress-induced velocity change, 22,40,41 temperature variation, 4244 water saturation, 38,45 and early-stage damage. 22,23,46 The CWI method has also been applied for damage localization and imaging purposes.…”
Section: Coda Wave Interferometrymentioning
confidence: 99%
“…Various studies have shown the linear relationship between wave propagation velocity change and temperature variation. 42,43,49,50 Thus, the thermally induced velocity change during each truck position can be calculated by equation (4), where T(p) is the temperature at the time when the truck was placed in different positions p and Tstart is the temperature measured before the load test start…”
Section: Coda Wave Interferometrymentioning
confidence: 99%